«Alt er jo egeninnsats» – Kvinners vendepunkter bort fra kriminalitet - Katharina Gjeruldsen; Egil Jensen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Research has emphasised the importance of turning points in desistance from crime. The current study investigates turning points in women’s desistance. Turning points from offending were explored through life story interviews with 20 female ex-offenders. The results support an  inextricable link between substance use and crime, the former considered by the participants as their main problem, and crime as secondary to this. Agency playing a substantial role is supported in this study. Some regard prison sentences as an opportunity to get away from their current social environment as a pathway out of crime. Examining turning points reveals that the desistance process in many cases can be described as a «long and winding road», with several setbacks along the way. Turning points result from a complex interaction between agent and structure, and are sometimes difficult to delimit clearly in time.